ANALISIS MANAJEMEN ARUS LALULINTAS JALAN PEMUDA SEGMEN JALAN DEPAN MALL PARAGON SEMARANG - Ardiyanto, Farid; Indracahya, Prima; Irawati, Iin (FSTPT Indonesia, 2015)
Transportation needs will continue to increase along with the development of urban areas . If the transportation needs is not matched with the transportation infrastructure ( road network ) then the resulting transportation problem persists. To resolve the matter, should the holding of a good traffic management . From the results of the traffic survey was conducted over three consecutive days on jalan Pemuda , Paragon Mall frontage road segments at peak afternoon and through the analysis of performance data path , on jalan Pemuda , especially the frontage road segments Paragon Mall , which often occurs queue or delay vehicle as a result of the presence of obstacles samping.Metode used for analysis is the Indonesian Highway Capacity Manual ( IHCM ) 1997. The results of the performance analysis of survey data for three days on jalan Pemuda was nearing saturation , ie with a DS of 0.551 , 0.504 , 0.520 as the influence of the side friction.